2011
DOI: 10.1111/j.1440-1746.2011.06800.x
|View full text |Cite
|
Sign up to set email alerts
|

Endosonography‐guided fine needle aspiration cytology of intra‐abdominal lymph nodes with unknown primary in a tuberculosis endemic region

Abstract: Despite being in a highly endemic area, almost half of the patients studied have a non-tuberculosis etiology. EUS-FNA is a safe and accurate procedure for establishing the diagnosis of unexplained intra-abdominal lymphadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
5
20
0
1
Order By: Relevance
“…In addition, EUS combined with FNA has a well‐established role in diagnosis of nonmalignant, inflammatory conditions such as sarcoidosis, fungal infections, and tuberculosis . Dhir et al were able to obtain an adequate specimen for tissue diagnosis in 92.4% of patients with undiagnosed intra‐abdominal lymphadenopathy, which is comparable with our results. The largest proportion of our cohort of patients was referred for the evaluation of lymphadenopathy.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, EUS combined with FNA has a well‐established role in diagnosis of nonmalignant, inflammatory conditions such as sarcoidosis, fungal infections, and tuberculosis . Dhir et al were able to obtain an adequate specimen for tissue diagnosis in 92.4% of patients with undiagnosed intra‐abdominal lymphadenopathy, which is comparable with our results. The largest proportion of our cohort of patients was referred for the evaluation of lymphadenopathy.…”
Section: Discussionsupporting
confidence: 88%
“…Endoscopic ultrasonography is very operator‐dependent and thus is one of the limitations to our study. Previous studies have shown that sufficient material for diagnosis of malignancy in EUS‐FNA of lymph nodes is usually obtained after 3–4 passes9–12 and this study confirms that inference with 87% of biopsies being adequate as judged by an onsite pathologist.…”
Section: Discussionsupporting
confidence: 84%
“…In MTB endemic settings, anti-tubercular drugs may be initiated however this approach may risk adverse drug reactions and interactions, hepatotoxicity and miss other pathology (Mendelson 2007). Indeed, a study from India using EUS FNA to assess abdominal lymphadenopathy in HIV-uninfected patients, confirmed that almost half of the patients in this high endemic region were found to have non-tubercular pathology (Dhir et al 2011) Similarly, our study confirmed that 31% of HIV infected patients with enlarged nodes, even in a high endemic area such as South Africa, had reactive lymphadenopathy. This implies that empirical ATT, prescribed solely on the basis of the presence of enlarged lymph nodes, may be associated with considerable treatment-related risks and should consequently be avoided.…”
Section: Discussionmentioning
confidence: 99%